How do 5-year-olds understand questions? Differences in languages across Europe. Issue 3 (June 2016) - Sauerland, Uli; Grohmann, Kleanthes K.; Guasti, Maria Teresa; Anđelković, Darinka; Argus, Reili; Armon-Lotem, Sharon; Arosio, Fabrizio; Avram, Larisa; Costa, João; Dabašinskienė, Ineta; de López, Kristine; Gatt, Daniela; et al.
The comprehension of constituent questions is an important topic for language acquisition research and for applications in the diagnosis of language impairment. This article presents the results of a study investigating the comprehension of different types of questions by 5-year-old, typically developing children across 19 European countries, 18 different languages, and 7 language (sub-)families. The study investigated the effects of two factors on question formation: (a) whether the question contains a simple interrogative word like 'who' or a complex one like 'which princess', and (b) whether the question word was related to the sentential subject or object position of the verb. The findings show that there is considerable variation among languages, but the two factors mentioned consistently affect children's performance. The cross-linguistic variation shows that three linguistic factors facilitate children's understanding of questions: having overt case morphology, having a single lexical item for both 'who' and 'which', and the use of synthetic verbal forms.